Clinical method of foetal weight estimation: a comparable alternative to ultrasound method in a low resource setting - Opara, Francis C.; Lohnan, Lucky C.; Abidemi, Tunde-Olatunji O.; Olubisi, Ojurongbe A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Foetal weight estimation is of utmost importance to obstetricians in the management of pregnant women during the antenatal and intrapartum period. This study aimed at determining reliable method of foetal weight estimation, (sonographic or clinical), that closely predicts the actual birth weight in booked pregnant women in Lafia, North Central, Nigeria. Methods: It was a cross-sectional comparative study carried out among 259 pregnant women recruited by consecutive sampling from September 2019 to January 2020 in the antenatal and labour wards of the hospital. The Dare’s formula was used to estimate the clinical foetal weight of the participants while the ultrasound foetal weight was estimated using the Hadlock 3 formula (BPD, AC and FL). The actual birth weight of each neonate was measured using the standardized Waymaster digital weighing scale. Qualitative variables were presented in means, median and standard deviation. Categorical variables were presented in frequencies and percentages. The absolute errors were tested with Chi square, paired t test, Mann Whitney U and Spearman’s rank correlation. A p<0.05 considered statistically significant. Results: The mean actual birth weight of neonates was 3074.5±398.4g. The results did not show any significant difference in the mean of estimated foetal weights using ultrasound and clinical methods when compared with the actual birth weights. Conclusions: There was no significant difference between the mean weight obtained through clinical and ultrasound estimation and actual birth weight. Clinical foetal weight estimation is as reliable as ultrasound weight estimation.